THE EFFECT OF PHYSICAL WORK ENVIRONMENT, WORK SAFETY, OCCUPATIONAL HEALTH AND WORK DISCIPLINE ON EMPLOYEE PRODUCTIVITY - RAHMI, TIKA ERRY; WIBOWO, SIGIT (JOURNAL OF RESEARCH IN MANAGEMENT, 2018)
Health and Work Discipline on Employee Productivity (Study on Employees of PT. PLN (Persero) Central Java & D.I.Y) Distribution Regulatory Areas". This study have a goal to determine and analyze the influence of the physical work environment, work safety, occupational health and work discipline on employee work productivity. The research was carried out on one of the owned companies that specialized in electricity in PT. PLN (Persero) APD Central Java and Yogyakarta Special Region. The research method used is a survey with judgment sampling sampling technique. The population in this study is PT. PLN APD Central Java and Special Region of Yogyakarta, the number of respondents taken in this research is 68 respondents. Based on the results of research and data analysis using Multiple Linear Regression Analysis shows that: (1) Physical work environment has a positive influence and significant effect on employee work productivity (2) Physical work environment has a positive influence and significant effect on employee work productivity (3) Work safety has a positive influence and significant effect on employee work productivity (4) Work discipline has a positive influence and significant effect on employee work productivity. The implication of this research is to continuously improve the work productivity of its employees, the management of PT. PLN (Persero) APD Central Java and Yogyakarta Special Region needs to maintain and improve various policies related to efforts to improve and improve the physical work environment, work safety, occupational health and employee work discipline.